2018
DOI: 10.5114/hpr.2018.75683
|View full text |Cite
|
Sign up to set email alerts
|

Exploring symptom expressions according to different age groups in fibromyalgia: a cross-sectional study

Abstract: health psychology report • volume 6(3), 8 original article background Fibromyalgia syndrome is a chronic musculoskeletal disorder which mostly affects women. This study investigates whether the prediction of self-report based fatigue, stress, everyday memory and impact (the most affected components of health status, i.e., physical impairment, feeling good, doing work, pain, anxiety, etc.) differ between younger patients and older patients with fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…However, the results of this study differ from some studies in the literature, which found that there are differences in the perception of fatigue among younger patients compared to older patients [ 26 , 28 , 29 ]. The study by Shillam, Jones, and Miller [ 26 ] made a comparison between the perception of FM symptoms between middle-aged adult patients and older patients, and the younger ones were found to be more symptomatic, that is, they had greater symptom intensity when compared to older patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results of this study differ from some studies in the literature, which found that there are differences in the perception of fatigue among younger patients compared to older patients [ 26 , 28 , 29 ]. The study by Shillam, Jones, and Miller [ 26 ] made a comparison between the perception of FM symptoms between middle-aged adult patients and older patients, and the younger ones were found to be more symptomatic, that is, they had greater symptom intensity when compared to older patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Shillam, Jones, and Miller [ 26 ] made a comparison between the perception of FM symptoms between middle-aged adult patients and older patients, and the younger ones were found to be more symptomatic, that is, they had greater symptom intensity when compared to older patients. Keskindag [ 28 ] in his study compared the perception of fatigue between three age groups (i.e., group 1 = 30–39-year-old patients; group 2 = 40–49-year-old patients; and group 3 = 50–59-year-old patients), and the authors concluded that younger patients (group 1) had higher levels of fatigue when compared to adults in the other groups. Similar findings to this were found by Jiao et al [ 29 ] when comparing fatigue-related symptoms between different age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is frequently observed in many diseases (e.g., cancer, neurodegenerative disorders, rheumatologic disease, heart failure) and can directly and indirectly affect the individual's health status and quality of life. Indeed, fatigue is a prolonged symptom in many neurologic and muscular disorders, such as multiple sclerosis, myasthenia gravis and fibromyalgia affecting both the psychological and the physical domain [11,12]. On the other hand, fatigue may be an isolated and persistent symptom with unknown etiology, the so-called "chronic fatigue syndrome" (CFS) [5,11].…”
Section: Overviewmentioning
confidence: 99%
“…The age group presented between patients in both samples should be considered as another limitation, since some studies [85,86] suggest that patients with younger ages tend to have higher levels of fatigue and lower levels of quality of life when compared to older patients. As a suggestion for future research, studies could be carried out on how age can influence the quality of life, fatigue, and levels of physical activity in patients with FM.…”
Section: Practical Implications and Limitationsmentioning
confidence: 99%